Pathological syndromes of the biliary tract decompression - Rasul T. Mejidov; Saadat Magomedova; Elmira P. Mamedova; Asli Z. Abdullaeva; Umukusum A. Nasibova (Клиническая практика, 2021)
Background: The increased incidence of cholelithiasis and tumoral lesions of the hepatopancreatoduodenal zone leads to an increase in the number of patients with obstructive cholestasis.